PENGGUNAAN DAN PENYIMPANGAN PRINSIP KESANTUNAN BERBAHASA PADA KOMENTAR KONTRA WARGANET DIKANAL YOUTUBE GITA SAFITRI DEVI DALAM KONTEN VIDEO “CHILDFREE: SERBA SALAH DIMATA WARGANET” - Ernawati, Ernawati; Prayitno, Harun Joko (Universitas Lampung, 2024)
This research aims to describe the usage and deviation of politeness in language in negative comments by netizens found in Gita Safitri Devi's YouTube video related to the content